Electrical and structural studies of polymer electrolyte based on chitosan/methyl cellulose blend doped with BMIMTFSI - Misenan M.S.M.; Isa M.I.N.; Khiar A.S.A. (Institute of Physics Publishing, 2024)
In this study, blended polymer electrolyte of methylcellulose (MC)/chitosan (CS) was prepared with different weight percentage of 1-butyl-3-methylimidazolium bis(trifluoromethyl sulfonyl) imide (BMIMTFSI) which acts as ion donor. This polymer blend was prepared by solution casting technique. The micro structure was observed by Field Emission Scanning Electron Microscopy (FESEM) where the multilayer could possibly be ascribed to the limited chain mobility. Sample having 60 wt% CS: 40 wt% MC was determined to have the most amorphous morphology extracted using deconvoluted data from x-ray Diffractography (XRD). Fourier Transform Infrared Spectroscopy (FTIR) peaks analysis shows the significant shift indicates complexation between ionic liquid and polymer backbone. The film was also characterized by impedance spectroscopy to measure its ionic conductivity. Samples with 45% of BMITFSI exhibit the highest conductivity of (1.51 0.13) 10-6 S cm-1 at ambient. Conductivity at elevated temperature was also studied, and the electrolytes obeys the Arrhenius behaviour. The conduction mechanism was best presented by small polaron hopping model. 2018 IOP Publishing Ltd.